2004
DOI: 10.1614/wt-03-167r
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide-Resistant Grass Weed Development in Imidazolinone-Resistant Wheat: Weed Biology and Herbicide Rotation

Abstract: A general life cycle model was modified to demonstrate how agronomic practices and weed biology factors affect the rate of appearance of herbicide-resistant downy brome, jointed goatgrass, and wild oat in Pacific Northwest wheat cropping systems. The model suggests herbicide rotation strategies for cropping systems that include imidazolinone-resistant wheat as a weed management tool. Simulation of continuous annual imidazolinone-resistant winter wheat and imazamox herbicide use resulted in the resistant soil s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Another simulation study predicted similar IMI-resistant A. cylindrica density in an IMI-resistant wheat–fallow rotation as with an IMI-resistant wheat–fallow–conventional wheat–fallow rotation (Rainbolt et al 2004). However, the total A. cylindrica seedbank in Rainbolt’s simulation was estimated to be much greater when conventional wheat was used, due to a lack of A. cylindrica control in the standard wheat crop.…”
Section: Biology and Ecologymentioning
confidence: 94%
“…Another simulation study predicted similar IMI-resistant A. cylindrica density in an IMI-resistant wheat–fallow rotation as with an IMI-resistant wheat–fallow–conventional wheat–fallow rotation (Rainbolt et al 2004). However, the total A. cylindrica seedbank in Rainbolt’s simulation was estimated to be much greater when conventional wheat was used, due to a lack of A. cylindrica control in the standard wheat crop.…”
Section: Biology and Ecologymentioning
confidence: 94%
“…Also, a study of imazapic showed that it is capable of eliminating many types of weeds, such as jointed goat grass and downy brome. Rainbolt et al (2004) reported that the herbicide imazamox D r a f t can eliminate the presence of red rice by up to 99%. In the USA, where the efficacy of the CPS system on diverse types of weeds that infest crops has been proven; for example, many weeds that infest rice, including barnyard grass (Echinochloa crus-galli), and severe types of weeds in wheat, such as cheat (Bromus secalinus L.) can be controlled.…”
Section: The Successful Story Of Imi Herbicides and Clearfield Rice Amentioning
confidence: 99%
“…In fact, growers and crop consultants can themselves use such models to evaluate and compare various weed management strategies on the long-term sustainability and profitability of farming operations. Rainbolt et al (2004) modified a general life cycle model into an extension teaching tool to demonstrate the effects of weed biology factors and crop rotation on resistance evolution in a number of major weed species in the Pacific Northwest dryland wheat-based cropping systems. Stanton et al (2008) developed a risk calculator to enable farmers and crop advisors assess the risk of glyphosate resistance evolution in annual ryegrass in Australia.…”
Section: Models As Educational Toolsmentioning
confidence: 99%